Accuracy of Mammography and Ultrasonography in Differentiating Benign and Malignant Breast Lesions Based on Histopathology at MRCCC Siloam Semanggi Hospital - Eben Haezer, Randi; Kusumaningtyas, Nungky; Muis, Mirna; Purwanto, Denni Joko; Lugito, Nata Pratama Hardjo; Supit, Nina ISH (Fakultas Kedokteran Universitas Pelita Harapan, 2026)
Background: Breast cancer is the most common malignancy in women. Early detection improves survival. Mammography is the gold standard for women over 40, while ultrasonography is commonly used in younger women with dense breasts. To compare the diagnostic accuracy of mammography and ultrasonography in differentiating benign and malignant breast lesions using histopathology as the Gold standard. Methods: This cross-sectional analytic study included 91 patients who underwent mammography, ultrasonography, and histopathological confirmation at MRCCC Siloam Semanggi Hospital. Diagnostic parameters including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), accuracy, and area under the curve (AUC) were calculated. Statistical analysis used McNemar’s test and ROC curve analysis based on Hanley & McNeil’s method, with p < 0.05 considered significant. Result: Ultrasonography demonstrated higher sensitivity (98.4%) and NPV (92.3%) than mammography (96.7% and 88.9%), indicating better ability to rule out malignancy. Mammography showed higher specificity (53.3% vs. 40.0%) and PPV (80.8% vs. 76.9%), reflecting better performance in identifying benign lesions. Overall accuracy was slightly higher for mammography (82.4%) compared to USG (79.1%). The AUC for mammography was 0.750 (95% CI: 0.630–0.870), while USG had an AUC of 0.692 (95% CI: 0.565–0.819). Overlapping confidence intervals indicated no statistically significant difference in diagnostic accuracy between the two modalities (p > 0.05). Conclusions: Mammography and ultrasonography both demonstrated high diagnostic performance with complementary strengths. Mammography provided higher specificity and PPV, while USG offered superior sensitivity and NPV. Given the small difference in accuracy and overlapping AUC confidence intervals, no significant difference was found between the two modalities. Combined use of mammography and USG may improve diagnostic accuracy in clinical practice.